An Analysis of the Impact of Financial Inclusion on Poverty and Development: Case of SACU Countries - Damiyano, David; Mago, Stephen (International Journal of Economics and Financial Issues, 2023)
Financial inclusion has been on the agenda as a vehicle of economic development in modern times. Studies base the contribution of financial inclusion on poverty and development on the theoretical and empirical evidence intensively expressed in literature. In some cases, the influence of financial inclusion on development has inconclusive effects on economic development and therefore, more and more research is underway to achieve an informed decision. This study attempted to relate financial inclusion to development and poverty in the SACU region. Financial inclusion is very vital for development and poverty reduction. The most financially excluded populations, the vulnerable, are found in developing countries and mainly women. The member states of the SACU region are also developing nations. The results of this study have indicated the importance of women’s education on financial literacy to enhance financial inclusion. There is also a need in the region to create employment opportunities for women so that they will be able to get access to formal financial institutions, for savings, bank accounts, withdrawals and salaries, which will in turn have a significant impact on financial inclusion. Poverty eradication or reduction is very critical in SACU region to enhance financial inclusion. The governments of the SACU member states must enact policies that are targeted at poverty eradication, which is in line with sustainable development goals, not just enacting, but in conjunction with implementation and close monitoring to make the policies effective.